The Paradox of Civil Society in the Structure of Hegel’s Views of Sittlichkeit - Avineri, Sholomo (Philosophy & theology, 1986)
The way in which much of the conventional interpretation has tried to describe the structure of Hegel’s civil society is inaccurate and one-dimensional. To Hegel civil society is not just the economic marketplace, where every individual tries to maximize his or her enlightened self-interest: side by side with the elements of universal strife and unending clash which are of the nature of civil society, there is another element which strongly limits and inhibits self-interest and transcends what would otherwise be a universal atomism into a sphere of solidarity and mutuality. The principle of civil society itself is dual. Hegel’s communitas grows organically within civil society itself, and is not imposed on it from outside by the state.